O5B.2 Dermal exposure to solvents: a need for quantitative analysis. (April 2019) - Duca, Radu-Corneliu; Moldovan, Horatiu; Creta, Matteo; Poels, Katrien; Voidazan, Septimiu; Godderis, Lode; Vanoirbeek, Jeroen
Abstract : For many years, airborne exposure was considered as the main work-related exposure and efforts have been made both on air monitoring and reduction of respiratory exposure. Nevertheless, recent studies have shown that preventive strategies with an exclusive focus on airborne exposures may falsely indicate a 'safe' environment. In 2014, WHO highlighted the importance of dermal exposure and its potential impact on human health. Moreover, it stipulated that the current technical and knowledge gaps related to the assessment of skin exposure have major lacunae. In this context, there is an increased demand for standardized methods and tools for measuring and assessing skin exposure to hazardous agents. We have developed an analytical method to simultaneously identify and quantify 195 volatile organic compounds (VOC) in dermal patches with activated charcoal cloth (ACC). Furthermore, we have done several field studies in different industrial settings, by the simultaneous assessment of dermal exposure using the ACC patches (on the hand, arm and neck), together with assessment of the respiratory exposure and determining the actual internal dose via urinary biomonitoring. Toluene, acetone and styrene exposure was found in a thermoplastic panel factory, styrene exposure in a composites body parts manufacturer, limonene and 1-methoxy-2-propanol exposure in a company that produces and prints plastic cartridges, and acetone and toluene in a pharmaceutical company. The results obtained from the quantitative ACC patches have been compared to the data obtained using Riskofderm for skin exposure, and the penetration through the skin was further estimated using IH-Skinperm and correlated with biomonitoring results. Based on the analytical development and the results of the different field studies, we can conclude that ACC patches represent a suitable technique to evaluate the deposition of VOCs on the skin. We further believe that assessing dermal exposure to solvents using ACC patches can substantially improve occupational health programs.